Preparation of protein isolated from rice bran - Mai Phuong, Nguyen Thi; Bac, Vo Hoai; Nhung, Tran Thi; Hiep, Do Hoang (Academia Journal of Biology, 2015)
Rice bran protein, a plant protein, has been recognized as nutritionally superior to other proteins due on its reported hypoallergenicity and anti-cancer activity. Therefore, it is considered as a promising protein resource applicable in variety of fields such as functional food, cosmetics, livestock and medicine. However, as of now, commercial rice bran protein is not widely available on the market, especially in Vietnam, because of a lack of extraction methods currently in use. In particular, the available methods can not be used to obtain protein isolates of high quality at affordable commercial price. Vietnam is one of the bigest rice export countries in the world, that makes rice bran an abundant agricultural by-product and thus, a readily sufficient source for protein extraction. This study aimed to establish a simple processing method for extraction of high content of protein isolates from rice bran. The obtained results indicated that rice bran was effectively hydrolysed in 20 minutes with α-amylase (Ternamyl) at concentration of 0.25%, pH 7.0 and 90oC. A procedure of 8 steps for protein extraction was given: i) Suspend rice bran in water and stir for 30 minutes at room temperature; ii) Adjust the suspension to pH 9.0 with NaOH 1N and stir for 4 hours; iii) Adjust the suspension to pH 7.0 with HCl 1N, add 0,25% Ternamyl at 90 oC and hydrolyse for 20 minutes; iv) Centrifuge at 4000 rpm for 20 minutes to collect the supernatant; v) Precipitate protein isolates at pH 4.0 by adding HCl 1N; vi) Centrifuge at 4000 rpm for 20 minutes to collect protein isolates; vii) Wash protein isolates twice with water; viii) Dry the isolates at 50oC. The content of protein isolates from this procedure was 41.77% and the yield of processing was 13,41%. The technological indexes including foaming capacity and emulsion activity were 20% and 73.50, respectively, which were higher compared to the same product from China.